"A Pot Full of Ancient Mysteries": An Australian Version of Attar's The Conference of the Birds - Aveling, Harry (Asiatic: IIUM Journal of English Language and Literature, 2018)
The thirteenth century Sufi text, The Conference of the Birds, describes a journey undertaken by a group of birds to find their king. It is an allegorical presentation of the mystical quest. The teachings are extensively illustrated by parables. An Australian Conference of the Birds, written in 1995 by Australian poet Anne Fairbairn (1928-), is a tribute to Attar’s poem, using Australian birds within an Australian bush setting. The poem also includes a quest for the King of the Birds. There are some important differences in the spirituality of the two poems. The Australian version places a lesser emphasis on the place of ethical behaviour in the life of the aspirant. There is little concern for the stages of growth in the development of mystical awareness. Successful completion of the quest itself is an individual physical achievement.